2020
DOI: 10.3390/agriculture10020035
|View full text |Cite
|
Sign up to set email alerts
|

Change of Price Premiums Trend for Organic Food Products: The Example of the Polish Egg Market

Abstract: One of the most rapidly growing areas of the organic agricultural system is egg production. However, the price premium often decreases the affordability of organic foods. In this study, the production and sales of organic eggs in Europe were compared, the prices of organic and conventional eggs in Poland were analyzed, and the price premium on the Polish market was evaluated. This study relied on data of Eurostat, Statistics Poland, Agricultural and Food Quality Inspection and Ministry of Agriculture and Rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 54 publications
(68 reference statements)
0
37
0
Order By: Relevance
“…1.8% of the total number of farms. The main factor behind the increase in the number of organic farms at that time was the high level of subsidization of this production system (Brodzinska, 2015), which unfortunately did not translate measurably into an increase in the domestic supply of organic food (Pawlewicz, 2020). In the case of Poland, the real possibilities of increasing the number of organic farms linked to the market have been largely exceeded, which is why since 2012 both the number and area of organic agricultural land has fallen.…”
Section: Resultsmentioning
confidence: 99%
“…1.8% of the total number of farms. The main factor behind the increase in the number of organic farms at that time was the high level of subsidization of this production system (Brodzinska, 2015), which unfortunately did not translate measurably into an increase in the domestic supply of organic food (Pawlewicz, 2020). In the case of Poland, the real possibilities of increasing the number of organic farms linked to the market have been largely exceeded, which is why since 2012 both the number and area of organic agricultural land has fallen.…”
Section: Resultsmentioning
confidence: 99%
“…Literature suggests that the majority of consumers have a positive attitude towards organic food, but few purchase it on a regular basis due to the price premium attached to it (Aertsens et al, 2009;Magnusson, 2004;Nguyen et al, 2019;Raza et al, 2019). Several studies (for instance, Marian et al, 2014;Melovic et al, 2020;Paul & Rana, 2012;Pawlewicz, 2020;Shafie & Rennie, 2012;Stolz et al, 2011) have observed that price premium is one of the main obstacles in the purchase of organic food, while the studies of (Aguilar & Vlosky, 2007;Dipeolu et al, 2009;Govindasamy et al, 2006;Obayelu et al, 2014;Owusu & Owusu Anifori, 2013;Saphores et al, 2007) argued that consumers are willing to pay more for organic food to some extent.…”
Section: Willingness To Paymentioning
confidence: 99%
“…Meat obtained from hens after the end of laying in intensive rearing conditions cannot compete with meat obtained from slaughter chickens, because it is meat from hens slaughtered at the age of several dozen weeks and is a by-product in the production of table eggs [ 1 , 2 , 3 ]. In recent years, an increase in the number of laying hens kept on organic farms has been observed in the EU countries [ 4 ]. Most often, hens of native breeds that are well adapted to local conditions are used for breeding under organic conditions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%